On Chilean Acting Training; Interview with Cristian Lagreze - Losada, Macarena (Latin American Theatre Review, 2025)
Since the 1980s, European techniques have had a significant impact on actor training in Chile; however, with the restoration of democracy in the 1990s, actor training started to change. Prominent professionals such as Cristian Lagreze, who received his training outside, have brought fresh perspectives to the Chilean setting. Lagreze talks about his experience as an actor in this interview, beginning at the University of Chile. He notes that the training process, which is moulded by emotional and physical conditioning particular to the sociological and cultural dynamics of today, aids trainers in developing a sense of identity and community. Students’ relationships with their bodies in training are being impacted by modern challenges like the effects of technology, capitalist pressures, and the increased awareness of gender and body politics. Lagreze also draws attention to the difficulties caused by the commercialisation of education, which makes students feel like customers. His observations highlight the difficulties involved in actor training in Chile and show how instructors must strike a balance between teaching conventional methods and the changing demands of contemporary actors.